Hi I am looking at an equation and would like to simplify my equation

If we calculate the heat removed in the hot water circuit of the heat exchanger and the heat gained in the sludge circuit of the heat exchanger we can work out the heat exchanger efficiency. The calculation looks like this -

(s)C_p*(s)M*(s)dT/(hw)C_p*(hw) M*(hw)dT*100 = Heat Exchanger Efficiency

(s)= sludge

(hw)= hot water

dT = change in temperature

C_p= heat capacity

M = Litres of water in relevant circuit of heat exchanger

Thanks for your help.

Peter